Analisis Penilaian Ranah Afektif Melalui Pembelanjaran Daring Mahasiswa Program Sarjana Era Digital - Soro, Suharyanto H.; Prapitasari, Tita (LP. Ma'arif Janggan Magetan, 2024)
Affective domain assessment is one of the activities carried out by lecturers in order to measure and determine the achievement of learning objectives. The affective domain is related to the attitudes and behavior of students as educated people in interacting with lecturers, other students and their environment. Disharmony between lecturers and students in the lecture process is the problem that is the object of this research. This is concrete evidence of the application of the affective domain. The aim of this research is to find out and describe the extent of the positive contribution of the affective domain in online learning for undergraduate students in the digital era. This research includes qualitative research with a case study approach. Data collection methods use observation, interviews and questionnaires. The number of samples in this research was 35. These samples were students from the Faculty of Economics in the first semester of the 2024 academic year. The results of the research showed that students from the Faculty of Economics Undergraduate Program preferred offline learning or face-to-face learning in class compared to online learning. Students experience a decrease in their caring values ​​for their lecturers because they do not receive direct touch or interaction through in-class (offline) learning.